2017
DOI: 10.1021/acs.nanolett.7b03829
|View full text |Cite
|
Sign up to set email alerts
|

Janus Iron Oxides @ Semiconducting Polymer Nanoparticle Tracer for Cell Tracking by Magnetic Particle Imaging

Abstract: Iron oxides nanoparticles tailored for magnetic particle imaging (MPI) have been synthesized, and their MPI signal intensity is three-times that of commercial MPI contrast (Ferucarbotran, also called Vivotrax) and seven-times that of MRI contrast (Feraheme) at the same Fe concentration. MPI tailored iron oxide nanoparticles were encapsulated with semiconducting polymers to produce Janus nanoparticles that possessed optical and magnetic properties for MPI and fluorescence imaging. Janus particles were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 46 publications
3
156
0
Order By: Relevance
“…Ferucarbotran nanoparticles have a mean hydrodynamic diameter of 62 nm, an r1 relaxivity of 7.2 ± 0.1 mM −1 s −1 and an r2 relaxivity of 82.0 ± 6.2 mM −1 s −1 at 1.5 Tesla and 37 degree Celsius [24]. Ferucabotran has been used extensively for clinical MRI [23, 25], but has been withdrawn from the US clinical market and recently reformulated for pre-clinical MRI and MPI applications [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferucarbotran nanoparticles have a mean hydrodynamic diameter of 62 nm, an r1 relaxivity of 7.2 ± 0.1 mM −1 s −1 and an r2 relaxivity of 82.0 ± 6.2 mM −1 s −1 at 1.5 Tesla and 37 degree Celsius [24]. Ferucabotran has been used extensively for clinical MRI [23, 25], but has been withdrawn from the US clinical market and recently reformulated for pre-clinical MRI and MPI applications [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, ferumoxytol is immediately clinically available for imaging applications in patients through an “off label” use. While initially not detectable with MPI, improvements of the MPI technology recently enabled detection of ferumoxytol nanoparticles in vitro [16]. It is not known, if MPI is sensitive enough to detect ferumoxytol labeled stem cells in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…With the optimal performance dictated by the magnitude of the superparamagnetic moment and uniform crystal size, attempts are underway to develop fine-tuned SPIO formulations with optimal MPI properties for cell tracking. One example is to synthesize Janus iron oxide nanoparticles that are three times more effective compared to Resovist and 7 times more compared to Feraheme [25]. It has been reported that MPI can have extreme high sensitivity, in the order of <1 pg within the entire FOV [26].…”
Section: Spios As Mpi Tracersmentioning
confidence: 99%
“…Small relaxation changes can be detected via color MPI, but even standard MPI can detect large relaxation changes 52• . MPI has seen only limited research into targeted nanoparticle coatings that target specific pathophysiologies 53•,54 . It will be exciting to see the vast area of nanomedicine research applied to MPI-targeted SPIOs for high specificity and sensitivity diagnosis of disease with zero ionizing radiation.…”
Section: Tracer Developmentmentioning
confidence: 99%
“…Mice were subcutaneously implanted with nanoparticle-labeled cells and imaged under MPI, fluorescence and T2-weighted MRI. Adapted with permission from 53• . Copyright 2017 American Chemical Society.…”
Section: Figurementioning
confidence: 99%